(untitled) (The Pakistan Development Review, 2009)
The purpose of this paper is to discuss the importance of incorporating asset holding and its distribution into the study of growth-equity relationship in the context of regional disparity. We have tried to discuss this issue by taking the Inclusive Growth Strategy (IGS) introduced by the Union Government of India in 2006. Although it is too early to assess the impact of IGC at this stage, the followings are some of the important findings of our analysis. First, the performance of the post-reform period is characterised by the higher economic growth and declining poverty ratio on one hand, and the increasing disparity in terms of consumption, income and asset holding on the other. Second, the magnitude of poverty and disparity is much more evident in asset holding, notably land, as compared with consumption and income, among economically and socially disadvantageous segments of rural communities. Third, if the inherent social inequality were overcome in the growth process, access to asset, notably land, has to be facilitated either by political process or through market transaction. In either case, the prospective is not yet bright. The paper strongly advocates, among others, the necessity of incorporating incomeasset relationship and structural aspects in discussing poverty and disparity issues in development. Keywords: Growth-Poverty Linkage, Income-Asset Relationship, Inherent Social Inequality, Inclusive Growth Strategy, Land Market, Capital Gain, Land Reform, Rent-land Price Ratio, Ginicoefficient.